2016
DOI: 10.1111/jfpp.12722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Enzyme Liquefaction Treatment on Major Carotenoids of Carrot (Daucus carrot L.) Juice

Abstract: The effect of enzyme liquefaction treatment on the content of a-carotene, b-carotene and lutein in carrot juice was investigated. The results of single factor experimental and orthogonal test indicated that the optimum condition of pectinase liquefaction were 1.5% pectinase worked for 120 min in condition of 45C and pH 5.0, while the optimum condition for cellulose liquefaction were 1.5% cellulose treated for 60 min in condition of 50C and pH 5.0. In addition, we could draw a conclusion that pectinase or cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…As described before, it could be about the degradation of the cell wall matrix which consists of pectin, cellulose, hemicellulose, and lignin by pectinolytic, cellulolytic, and mannanase enzymes. These results are in agreement with the researches about the carrot juice maceration with more than one enzyme (Demir et al, 2007;Liao et al, 2007;Ma et al, 2016;Sun et al, 2006). The effects on the yield and quality of carrot juice produced with and without total enzymatic liquefaction (Pectinex Ultra SP-L) showed that it was improved β-carotene concentrations but the processes without enzyme treatment improved β-carotene content much more than enzyme-treated samples (Demir et al, 2007).…”
Section: Effect Of Enzyme Pretreatment On Turbidity and β-Carotene Values Of The Carrot Juicesupporting
confidence: 90%
See 3 more Smart Citations
“…As described before, it could be about the degradation of the cell wall matrix which consists of pectin, cellulose, hemicellulose, and lignin by pectinolytic, cellulolytic, and mannanase enzymes. These results are in agreement with the researches about the carrot juice maceration with more than one enzyme (Demir et al, 2007;Liao et al, 2007;Ma et al, 2016;Sun et al, 2006). The effects on the yield and quality of carrot juice produced with and without total enzymatic liquefaction (Pectinex Ultra SP-L) showed that it was improved β-carotene concentrations but the processes without enzyme treatment improved β-carotene content much more than enzyme-treated samples (Demir et al, 2007).…”
Section: Effect Of Enzyme Pretreatment On Turbidity and β-Carotene Values Of The Carrot Juicesupporting
confidence: 90%
“…The other research about carrot juice also showed that pectinase or cellulase treatment could significantly improve the carotenoid concentrations (Lutein, α-carotene, and β-carotene) on the results of different enzyme liquefaction treatments and the SEM observation of carrot juice. Composite enzyme treatment with non-equal proportion (pectinase and cellulose) could also significantly improve the three carotenoids concentration (p < .05) (Ma et al, 2016). CCRD optimization was also performed and increased the β-carotene content (≥54.2 mg/kg) with an usage of 100 ml/t of enzyme concentration and 80 min incubation time (Sun et al, 2006).…”
Section: Effect Of Enzyme Pretreatment On Turbidity and β-Carotene Values Of The Carrot Juicementioning
confidence: 97%
See 2 more Smart Citations
“…β -carotene that is released from the protective chromoplast structures during this time is further exposed to the conditions of the external environment. These can undergo rapid oxidative degradation, and this may lead to reduction in β -carotene content (Choudhari and Anathanarayan, 2007; Lenucci et al , 2015; Ma et al , 2016).…”
Section: Resultsmentioning
confidence: 99%